TALE HAJI KERINCI: STRUKTUR, LINGKUNGAN PENCERITAAN DAN FUNGSI SOSIAL TEKS - Suci Maiza (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2023)
The reseach has describing the structures, storytelling environment and social function of Tale Haji Kerinci text. This research is a qualitative descriptive study using a content analysis method to insvestigate the content and information contained in Tale Haji text. while the data collection technique is done by observation technique through recording and note taking, as well as interview technique that is carried out on informants such as traditional leaders and community leaders. The research finding revealed that the structures of Tale Haji Kerinci are in the form poem as rows and lines rhyme, sampiran and the content and word choice, environmental of Tale Haji is include sad and happines. The function of Tale Haji Kerinci as educated and religius function.